Trends of shoulder instability surgery in Finland: a nationwide register study - Antti Joukainen; Ville M Mattila; Vesa Lepola; Janne Lehtinen; Juha Kukkonen; Juha Paloneva (BMJ PUBLISHING GROUP, 2022)
Objective Rate of shoulder instability surgery (SIS) has increased in different specific populations. We analysed nationwide trend of SIS in adults in Finland between 1997 and 2014. Design A retrospective register study. Setting National Hospital Discharge Register of Finland. Participants A total of 22 550 adult patients with SIS in Finland (1997-2014). Primary and secondary outcome measures Analysis included appropriate diagnosis (International Classification of Diseases 10) and procedure coding combinations applicable for SIS. The primary outcome variable was the incidence of SIS per 100 000 person-years, and the secondary outcomes were the study year, sex, age groups (18-29, 30-49 and over 50 years of age) and the type of hospital (public or private). Results The overall nationwide rate of SIS in adults increased 177% between 1997 and 2014 in Finland. The rate was the lowest (13/100 000 person-years) in 1997, and the peak rate (40/100 000 person-years) was noted in 2007. The increase in rate was rapid between 1997 and 2007, after which the rate became stable. During the study period, the highest increases were noted in the young adults age group (270%), and especially in the middle-aged group who were operated on in private hospitals (930%). Conclusions The rate of SIS increased almost threefold in Finland from 1997 to 2014. The increase was most significant in young and middle-aged adults (18-50 years), in men, and in private hospitals.